Balancing the development agenda : (The World Bank, 2005)
Balancing the Development Agenda examines the evolution of the World Bank and its operations during the presidency of James Wolfensohn. It examines the modernization of this global economic institution which is now focused on home-grown development planning where borrowing countries are in the driver's seat of their own development. It takes a closer look at the major development challenges addressed by the Bank during the past decade such as debt relief, corruption, and HIV/AIDS and provides a timeline of events that have shaped the Bank into the institution it is today.